Impact of The Penetration of Renewable Energy on Distributed Generation Systems - Oyinlolu Ayomidotun Odetoye; Oghenewvogaga Oghorada; Adeleke Olusola Alimi; Babatunde Adetokun; Uchenna Nnaemeka Okeke; John Obiajulu Onyemenam; Paul Kehinde Olulope; Matthew Olabisi Olanrewaju (Majlesi Journal of Electrical Engineering)
As the proportion of total generation by renewable sources compared to non-renewable sources increases, the relative inertial stability provided by large rotating generators in electricity grids is found to shrink and is not being replaced by sources such as photovoltaic and wind power, which are already known for their inherent variability. This leads to electricity generation systems being less stable, less flexible, and less adequate in applications with a high diversity factor, and literature shows that the penetration of renewable energy sources in distribution-generation/microgrid system frequently presents several technical and economic challenges in their usual applications. This work examines how increased renewable energy penetration impacts the distribution-generation system and suggests approaches and measures for tackling the challenges that are associated with it.